PENGARUH CITRA MEREK, KEPERCAYAAN MEREK, PROMOSI DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PENGGUNAAN JASA GOJEK Studi Kasus Pada PT. Aplikasi Karya Anak Bangsa di Kota Banjarmasin - Arif Rahman (At-Tadbir : jurnal ilmiah manajemen, 2020)
This study aims to examine and analyze the influence of Brand Image, Brand Trust, Promotion, and Consumer Value on the Decision to Use Services by GOJEK consumers in Banjarmasin City. The data collection method in this study used a questionnaire distributed to 160 respondents with the unit of analysis being consumers who were 17 years old and had used GOJEK services in the form of Go-ride, Go-car, or Go-food at least 1 time. The data collected is then performed multiple linear regression analysis is a data analysis method used in this study. The results of this study indicate that Brand Image, Brand Trust, Promotion, and Consumer Value significantly influence the Decision to Use Services by GOJEK consumers. Nevertheless, the best results in describing purchasing decisions are given sequentially by customer value, brand trust, brand image, and promotion. A detailed discussion will be discussed at the end of this study.Keywords: brand image, brand trust, promotion, customer value, service use decisions